MENINGKATKAN KOSA KATA SISWA SMP 4 MANGARABOMBANG MELALUI MEDIA CERITA RAKYAT - Adni Dzilarsy Makina; Aprilia Ningsi; Ariana Ariana (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
Vocabulary mastery is a major challenge for students at SMP 4 Mangarabombang, where conventional methods often fail to create meaningful learning. This study aims to improve students' English vocabulary mastery through the use of folklore media. By integrating local wisdom, students are expected to more easily absorb new words in familiar contexts. This study uses a quantitative approach with a Pre-Experimental design (One-Group Pretest-Posttest Design). The research subjects consisted of 30 eighth-grade students selected through a purposive sampling technique. Data were collected through a vocabulary test instrument and analyzed using a paired sample t-test. The results showed a significant increase in students' vocabulary skills, where the average score increased from 54.20 in the pre-test to 82.50 in the post-test. Statistical analysis showed a significance value of 0.000 0.05, which means the alternative hypothesis is accepted. In addition, the percentage of learning completeness increased drastically from 20% to 90%. The conclusion of this study is that folklore media is effective in increasing students' vocabulary because it can reduce affective barriers and increase mental engagement through a culturally relevant context. These results recommend that educators use local culture-based materials as an innovation in English teaching.